2015
DOI: 10.1007/s11882-014-0501-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Influences over Offspring Allergic Responses

Abstract: Asthma occurs as a result of complex interactions of environmental and genetic factors. Clinical studies and animal models of asthma indicate offspring of allergic mothers have increased risk of development of allergies. Environmental factors including stress-induced corticosterone and vitamin E isoforms during pregnancy regulate the risk for offspring development of allergy. In this review, we discuss mechanisms for the development of allergic disease early in life, environmental factors that may impact the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 112 publications
(130 reference statements)
1
32
0
1
Order By: Relevance
“…Other epigenetic modifications, such as histone modification, noncoding RNAs, chromatin remodeling, may be responsible for the changes of Treg cells too. Previous researches indicated that classic genetic inheritance4344 and perinatal transfer of maternal mediators (such as allergens, antibodies or cytokines) via placenta or breast milk454647 might also be responsible for maternal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Other epigenetic modifications, such as histone modification, noncoding RNAs, chromatin remodeling, may be responsible for the changes of Treg cells too. Previous researches indicated that classic genetic inheritance4344 and perinatal transfer of maternal mediators (such as allergens, antibodies or cytokines) via placenta or breast milk454647 might also be responsible for maternal effect.…”
Section: Discussionmentioning
confidence: 99%
“…4-5 mg alpha-tocopherol per day during lactation. A recent study has also shown a link between low vitamin E intake and miscarriages during the first trimester of pregnancy, pointing to the importance of adequate intake in women of child bearing age [22]. We respectfully disagree with the Panel's conclusion, that "a full compensation of the transitory secretion of alpha-tocopherol in breast milk is not justified for the derivation of DRVs for alpha-tocopherol for lactating women."…”
Section: Organisationmentioning
confidence: 70%
“…A recent study has also shown a link between low vitamin E intake and miscarriages during the first trimester of pregnancy, pointing to the importance of adequate intake in women of child bearing age [4]. A link between maternal alpha-tocopherol levels and development of asthma and allergies in the offspring has also been reported by several studies [22]. Therefore it is important to consider all the above data to set the adequate intake for the health of both mother and child.…”
Section: Organisationmentioning
confidence: 95%
“…Two recent reviews comprehensively summarized the state of the art on maternal influences on allergic responses in offspring, and discussed potential biological mechanisms [2,3]. Maternal effects on Th1 and Th2 cytokines in the offspring, as well as maternal vitamins as regulators of offspring allergic responses were highlighted [2].…”
Section: Mechanisms For Prenatal Stress and Asthma Riskmentioning
confidence: 99%
“…Maternal effects on Th1 and Th2 cytokines in the offspring, as well as maternal vitamins as regulators of offspring allergic responses were highlighted [2]. It may also be important to consider how those maternal stress-related markers can be transferred to the fetus via the placenta.…”
Section: Mechanisms For Prenatal Stress and Asthma Riskmentioning
confidence: 99%